2004
DOI: 10.1038/sj.ijir.3901192
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave therapy for Peyronie's disease does not correct penile deformity

Abstract: To evaluate whether extracorporeal shockwave therapy (ESWT) offers an effective treatment for the main complications of Peyronie's disease (PD), that is, penile deformity and angulation, painful erection and most importantly unsatisfied sexual intercourse. From September 1999 to January 2001, 52 patients with PD were treated with ESWT. Pain during erection was assessed with a visual analogue scale. Penile deviation was determined by photographs with a goniometer. Five treatment sessions were performed at weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 16 publications
1
22
0
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] Many of the studies have been criticized for their lack of objectivity and relatively short follow-up periods (mean follow-up 1-9 months), and there is, therefore, a paucity of longterm data with regard to therapy effectiveness and safety. There also is a lack of information regarding the long-term durability of the response after initial success.…”
Section: Srirangam Et Al 882mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11] Many of the studies have been criticized for their lack of objectivity and relatively short follow-up periods (mean follow-up 1-9 months), and there is, therefore, a paucity of longterm data with regard to therapy effectiveness and safety. There also is a lack of information regarding the long-term durability of the response after initial success.…”
Section: Srirangam Et Al 882mentioning
confidence: 99%
“…The use of extracorporeal shockwave therapy (ESWT) for Peyronie's disease was introduced by Bellorofonte and associates 1 as a conservative option, and since then, numerous reports have addressed the efficacy of this treatment. [2][3][4][5][6][7][8][9][10][11] Reported results have been discordant, with some showing promising responses to ESWT with reductions in deformity, plaque size, and pain and concurrent improvement in sexual function, whereas others demonstrate no significant benefit. 8,10,11 In spite of reports of success and low complication rates, previous studies have been criticized for small patient numbers, absence of a control arm, use of subjective outcome measures, and lack of long-term follow-up.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have reported that ESWT was able to reduce both penile curvature and pain, improving the sexual function of PD patients [38] . An exploratory meta-analysis of clinical trials about the use of ESWT for PD did not reveal a clear effect on penile curvature, plaque size, and, most importantly, intercourse satisfaction.…”
Section: Energy Transfermentioning
confidence: 99%
“…Exact data on quantification of changes in plaque size were not provided in most studies. Only the two most recent studies (13,25) provided exact data on the change of plaque size. In these two studies, no significant changes of plaque size were observed in comparing the total number of patients before and after the intervention (13,25).…”
Section: Resultsmentioning
confidence: 99%
“…6. Only 5 of the 21 studies represent prospective controlled approaches according to their own definitions (12)(13)(14)17,23,25), and none is single blinded-real vs simulated ESWT -as described in orthopedic studies (33). A case-controlled design was only performed by 1 study group (12).…”
Section: Problems Of Interpretation and Comparisonmentioning
confidence: 99%